Effect of aqueous-phase processing on the formation and evolution of organic aerosol (OA) under different stages of fog life cycles. (1st June 2019) - Mandariya, Anil Kumar; Gupta, Tarun; Tripathi, S.N.
Abstract: Secondary organic aerosol (SOA) is a significant component of organic aerosol (OA), formed majorly via aqueous-phase processing (aqSOA) during winter fog period yet it persist as a significant source of uncertainties within climate models due to lack of sufficient knowledge about its ambient formation and evolution processes. Kanpur is situated at the center of Indo-Gangetic Plain which witnesses several fog episodes every year during winter time. In this study, we have evaluated the effect of aqueous-phase processing on the formation pathway of OA, its composition and oxidative properties during five fog processing periods, i.e., Pre-Fog-Period (Pr-F-P), Activating-Fog-Period (A-F-P), Fog-Period (F-P), Dissipating-Fog-Period (D-F-P), and Post-Fog-Period (Po-F-P). A-F-P was observed as heavily polluted period (249.8 ± 47.8 μg/m 3 ) while F-P period was least polluted (153.1 ± 37.8 μg/m 3 ) indicating the wet removal through grown fog droplets. Oxygenated organic aerosol (OOA-1) processed mainly through biomass burning (BB) emission suggesting is a good surrogate of aqueous SOA, and it gets enhanced significantly during high biomass-burning emissions during A-F-P and D-F-P under acidic aerosol conditions. Also, in contrast to formation mechanism, our results proposing specific formation process (fragmentation, functionalization, or oligomerization) for different fog processing periods. A-F-P and D-F-P periods are crucial possibly for the formation of OA dominant through oligomerization mechanism in which functionalization of OH moieties occurs in A-F-P periods, whereas oligomerization mechanism with the addition of carbonyl (aldehyde/ketone) moieties could occur in D-F-P periods, accompanied by acidic aerosol as well as high aerosol liquid water content (ALWC). In contrast, during OA evolution process, Van Krevelen (VK) slope, O/C ratio, SOA O/C ratio (O/COOA ), average oxidation state of carbon for bulk-aerosol (OSC ) and SOA (OSC )OOA, substantially varies throughout all the fog processing periods. Graphical abstract: Image 1 Highlights: Chemical speciation and oxidative properties of OA were assessed under different stages of fog life cycles. Oligomerization and functionalization mechanisms were suggesting dominated the formation of OOA during A-F-P and D-F-P. Fragmentation and functionalization mechanisms governed the formation of OOA during F-P and Po-F-P. Both activation as well as dissipating fog processing periods have acidic aerosol and high aerosol liquid water content.